SOSIALISASI UNDANG-UNDANG NOMOR. 44 TAHUN 2008 TENTANG PORNOGRAFI DI KALANGAN MAHASISWA - SUPRIYANTA, SUPRIYANTA; Kusumo, Bambang Ali (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
The aim of this community service activity is to provide an explanation to students regarding the criminal provisions in Law no. 44 of 2008 concerning Pornography and building positive perceptions and behavior of students related to pornography issues. Pornography is prohibited in the law, intended as a way to prevent the younger generation, including students, from doing things that are prohibited in the law. In theory, this idea is supported by von Fuerbach's theory of psychological coercion, namely prohibitions and threats. Criminal law will prevent people from committing acts that are prohibited by law. The method used in this service activity is the lecture method by opening up space for discussion. The results of community service showed that based on the explanation given to the students who were the target of this activity, the majority of students were satisfied with the activity. With this activity, students became aware of how important the existence of a law is. Knowledge of criminal sanctions has influenced their psychology to obey the law. Thus, the theory of psychological coercion states that the existence of criminal sanctions in the law has influenced the psychology of members of society so that they are prevented from committing crimes. Apart from that, awareness has also arisen to participate in preventing and taking action against pornography cases. Keywords: Socialization, Law Number 44 of 2008 concerning Pornography, Students.